Lower limit of hydrocarbon generation in source rocks: A case study from the Dongpu Depression, Bohai Bay Basin, East China. (15th September 2019) - Tang, Ling; Pang, Xiongqi; Song, Yan; Jiang, Zhenxue; Jiang, Shu; Li, Qianwen; Zhang, Hongan; Yang, Youdong; Li, Xiaohui
Graphical abstract: Based on the definition and theoretical model of the LLHG (a), four methods including hydrocarbon generation potential (b1 ), residual hydrocarbon amount (b2 ), organic element variation (b3 ) and expulsed hydrocarbon amount (b4 ) are used to calculate the value of LLHG, the results are verified by the thermal simulation experiment (c). Highlights: The lower limit of hydrocarbon generation (LLHG) is redefined and modeled. The LLHG is obtained based on methods of hydrocarbon generation potential and verified. The LLHG values in the north of Dongpu Depression are generally larger than those in the south. The main effect factors of LLHG are organic matter type and abundance, formation temperature and pressure. Abstract: With the increasing demand for hydrocarbons, exploration tends to be deeper and unconventional resources. However, whether there are the lower limits for exploration depth or thermal maturity (Ro ) appears to be particularly essential. It is of considerable significance to determine the lower limit of hydrocarbon generation (LLHG) since this limit can provide guidelines for hydrocarbon potential estimation. According to the mechanisms of hydrocarbon generation and expulsion, five methods are combined to determine and verify the LLHG, whose values can be expressed by LLHG(Ro) and LLHG(H) . Source rock samples from the Paleogene Shahejie Formation (Es) in the Dongpu Depression were taken as an example to determine the LLHG, and then controlling factors of the LLHG were discussed. LLHG(Ro) values for Es range from 3.23% to 3.97% (average 3.71%) and LLHG(H) values range from 5244 m to 5525 m (average 5433 m). Regionally, LLHG values display obvious differences between the northern and southern of depression. LLHG values in the north are roughly larger than those in the south. In the northern depression, the LLHG(Ro) values are ranging from 3.61% to 3.97% (average 3.81%) and LLHG(H) values are ranging from 5415 m to 5545 m (average 5488 m). However, in the southern part, the LLHG(Ro) values range from 3.20% to 3.74% (average 3.48%) and the LLHG(H) values range from 5265 m to 5375 m (average 5278 m). The main controlling factors for LLHG diversity between the north and the south of depression are organic matter (OM) type and abundance, formation temperature and pressure.